2008
DOI: 10.1038/ja.2008.41
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Macrolide Antibiotic-binding Human_p8 Protein

Abstract: Clarithromycin is a macrolide antibiotic that is widely used in clinical medicine. Macrolide antibiotics such as clarithromycin specifically bind to the 50S subunit of the bacterial ribosome thereby interfering with protein biosynthesis. A selected peptide sequence from our former study, composed of 19 amino acids, which was isolated from a phage display library because of its ability to bind clarithromycin, displayed significant similarity to a portion of the human_p8 protein. The recombinant p8 protein binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Tetracyclines, macrolides and ketolides display potent anti‐inflammatory activities (Tamaoki et al ., 2004; Weinberg, 2005; Del Rosso, 2007; Webster and Del Rosso, 2007; Leiva et al ., 2008a,b) while rifampin exerts the opposite effect (Yuhas et al ., 2008). The macrolide antibiotic‐binding human p8 protein was recently cloned and identified using the phage display library approach (Morimura et al ., 2008). This is a nuclear DNA‐binding protein, which is strongly activated in response to several stresses, and, on the basis of functional similarity to HMG‐I/Y‐like proteins, it was suggested that p8 may be involved in transcription regulation (Encinar et al ., 2001; Hoffmeister et al ., 2002).…”
Section: Phenotypic Responses To Antibiotic Signallingmentioning
confidence: 99%
See 2 more Smart Citations
“…Tetracyclines, macrolides and ketolides display potent anti‐inflammatory activities (Tamaoki et al ., 2004; Weinberg, 2005; Del Rosso, 2007; Webster and Del Rosso, 2007; Leiva et al ., 2008a,b) while rifampin exerts the opposite effect (Yuhas et al ., 2008). The macrolide antibiotic‐binding human p8 protein was recently cloned and identified using the phage display library approach (Morimura et al ., 2008). This is a nuclear DNA‐binding protein, which is strongly activated in response to several stresses, and, on the basis of functional similarity to HMG‐I/Y‐like proteins, it was suggested that p8 may be involved in transcription regulation (Encinar et al ., 2001; Hoffmeister et al ., 2002).…”
Section: Phenotypic Responses To Antibiotic Signallingmentioning
confidence: 99%
“…This is a nuclear DNA‐binding protein, which is strongly activated in response to several stresses, and, on the basis of functional similarity to HMG‐I/Y‐like proteins, it was suggested that p8 may be involved in transcription regulation (Encinar et al ., 2001; Hoffmeister et al ., 2002). Since clarithromycin, erythromycin and azithromycin inhibit the binding of recombinant p8 protein to double‐stranded DNA (Morimura et al ., 2008), the anti‐inflammatory effect of macrolides may be explained by the downregulation of transcription of genes involved in the pro‐inflammatory network. Interestingly, the same inhibitory effect was observed with a structurally unrelated antifungal antibiotic dechlorogriseofulvin (Morimura et al ., 2008) suggesting a potential overlap in recognition of structurally different antibiotic ligands by a single human molecular sensor.…”
Section: Phenotypic Responses To Antibiotic Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…The macrolide antibiotic-binding human p8 protein has been cloned and identified using the phage display library approach (Morimura et al, 2008). This is a nuclear DNA-binding protein, which is strongly activated in response to several stresses, and, on the basis of functional similarity to HMG-I/Y-like proteins, it has been suggested that p8 may be involved in transcription regulation (Encinar et al, 2001; Hoffmeister et al, 2002).…”
Section: Macrolidesmentioning
confidence: 99%
“…In cardiac pathology, p8 is broadly involved in cellular events leading to cardiomyocyte hypertrophy and cardiac fibroblast MMPs production, both of which take place in heart failure (Goruppi et al, 2007). Since clarithromycin, erythromycin, and azithromycin inhibit the binding of recombinant p8 protein to double-stranded DNA (Morimura et al, 2008), the anti-inflammatory effect of macrolides discussed above may be explained, at least in part, by the down-regulation of transcription of genes involved in the proinflammatory network. Interestingly, the same inhibitory effect has been observed with a structurally unrelated antifungal antibiotic dechlorogriseofulvin (Morimura et al, 2008), suggesting a potential overlap in recognition of structurally different antibiotic ligands by a single human molecular target.…”
Section: Macrolidesmentioning
confidence: 99%